The effects of increasing concentrations of Trichanthera gigantea leaves in pellets on the nutritive value and short-term intake of diets of grass plus pellets offered to lambs reared under tropical conditions in the Caribbean - Jack HA; Cranston LM; Burke JL; Knights M; Morel PCH (Centro Internacional de Agricultura Tropical, 2021)
There is currently limited information on the benefits of increasing the concentration of Trichanthera gigantea leaves in pelleted diets offered to lambs reared under tropical conditions in the Caribbean. Twelve crossbred Barbados Blackbelly rams aged 5 months were used to determine the effects of increasing the concentrations of T. gigantea in pelleted diets, on the nutritive value and intake of grass forage plus pellets offered to lambs. Animals were randomly assigned to a basic diet (4 kg) of chopped Cenchrus purpureus plus 1 of 6 pelleted diets (500 g) comprised of either 100% intact commercial pellets or a pelleted mixture of ground commercial pellets and ground (dry fallen) T. gigantea leaf in the following ratios (T. gigantea leaves:ground commercial pellets): 20:80 (T20); 40:60 (T40); 60:40 (T60); 80:20 (T80); and 100:0 (T100). Total intakes of forage and pellets (TPI) were measured at the end of each day during a period of 7 days, and the average daily nutrient intakes of the different treatment diets were calculated. Overall, there was no significant difference in the intakes of pellets containing 0 to 80% T. gigantea leaves (P>0.05) but intakes of pellets comprising 100% T. gigantea leaves were significantly lower (P<0.0001). Both CP and soluble protein intakes declined progressively as the percentage of T. gigantea leaves in the pellets increased. While level of T. gigantea leaves in pellets fed to lambs did not generally affect total intakes of pellets, grass, or grass+pellets, animal performance on these various rations cannot be assumed to be similar until longer-term feeding studies have been performed, as reduced protein and energy concentrations in the pellets could significantly lower weight gains as level of leaf in the pellets increased.
Keywords: Barbados Blackbelly sheep; multi-purpose trees; pellet feeding